Effects of riverine suspended particulate matter on post-dredging metal re-contamination across the sediment–water interface. (February 2016) - Liu, Cheng; Fan, Chengxin; Shen, Qiushi; Shao, Shiguang; Zhang, Lei; Zhou, Qilin
Abstract: Environmental dredging is often used in river mouth areas to remove heavy metals. However, following dredging, high levels of metal-adsorbed suspended particulate matter (SPM) originating from polluted inflowing rivers might adversely affect the sediment–water interface (SWI). Here, we conducted a 360-day-long experiment investigating whether the riverine SPM adversely affects dredging outcome in a bay area of Lake Chaohu, China. We found that the heavy metal concentrations in the post-dredging surface sediment increased to pre-dredging levels for all metals studied (As, Cd, Cr, Cu, Ni, Pb, and Zn) after the addition of SPM. In addition, the increased concentrations were mostly detected in the relatively bioavailable non-residual fractions. Of the metals studied, the rate of increase was the greatest for Zn and Cd (482.98% and 261.07%, respectively), mostly in the weak acid extractable fraction. These results were probably due to certain characteristics of SPM (fine grain size, and high concentrations of organic matter and heavy metals) and the good oxic conditions of the SWI. Furthermore, As was the only metal for which we observed an increasing trend of diffusive flux across the SWI. However, the flux was still significantly lower than that measured before dredging. In conclusion, the quantity and character of riverine metal-adsorbed SPM affect metal re-contamination across the post-dredging SWI, and this information should be incorporated into the management schemes of dredging projects dedicated to reducing metal contamination in similar areas. Highlights: The riverine suspended particulate matter (SPM) was sampled and studied. The post-dredging sediment was re-contaminated with the influence of SPM. The re-contaminated metals were mostly detected in non-residual fractions. SPM regulates metal re-contamination and dredging effects in the confluence area.